Shivam finance : using fintech to consolidate and grow - Bohra, Shrenik; Sahay, Arvind; Tiwari, Tara (London : Indian Institute of Management, Ahmedabad, 2020)
Shivam Finance is a private lending firm operating in the Bhilwara district in Rajasthan. It offers loans for buying two-wheelers to customers of nearby districts. The firm applied for a non-banking financial company (NBFC) licence in 2019 as the lending regulations changed, and it became difficult for the firm to operate in the two-wheeler financing space as a private lending firm. With this licence, it plans to scale up its operations two times and adopt a fintech-based model for making its processes more efficient.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Financial institutions -- Management -- Case studies